COVID-19 in Latin America and the Caribbean: what is known about the status of school reopening? - Fernandez-Guzman, Daniel (2021)
Since December 2019, the world has been facing a rapid increase in cases and deaths from the new coronavirus (COVID-19), forcing a response from countries all over the world to stop its transmission. Thus, at the beginning of April, 172 nations closed their schools, affecting >84.8% (~1484 million) of students enrolled worldwide,1 aiming to reduce the exposure to the virus, a social measure previously used to control the H1N1 influenza pandemic.2